A Review and Comparison of the State-of-the-Art Techniques for Atrial Fibrillation Detection and Skin Hydration - Liaqat, Sidrah; Dashtipour, Kia; Zahid, Adnan; Arshad, Kamran; Ullah Jan, Sana; Assaleh, Khaled; Ramzan, Naeem (Frontiers in Communications and Networks, 2021)
Atrial fibrillation (AF) is one of the common types of cardiac arrhythmia with a prevalence of 1-2% in the community, increasing the risk of stroke and myocardial infarction. Early detection of AF, typically causing irregular and abnormally fast heart rate can help reduce the risk of strokes that are more common among older people. Intelligent models capable of automatic detection of AF in its earliest possible stages can improve the early diagnosis and treatment. Luckily, this can be made possible with the information about the heart’s rhythm and electrical activity provided through electrocardiogram (ECG) and the decision-making machine learning-based autonomous models. In addition, AF has a direct impact on the skin hydration level, hence, can be used as a measure for detection. In this paper, we present an independent review along with a comparative analysis of the state-of-the-art techniques proposed for AF detection using ECG and skin hydration levels. This paper also highlights the effects of AF on skin hydration level that is missing in most of the previous studies.